Adaptasi alat ukur kesuksesan karier subjektif - Tri Muji Ingarianti; Fendy Suhariadi; Fajrianthi Fajrianthi (Jurnal Ilmiah Psikologi Terapan, 2022)
Subjective career success is an attitude regarding an individual’s achievement and satisfaction with their career resulting from a personal evaluation of their career experience. Subjective career success has eight dimensions: recognition, quality work, meaningful work, influence, authenticity, personal life, growth and development, and satisfaction. Subjective Career Success Inventory – SCSI (Subjective Career Success Questionnaire) has 24 items. The use of instruments at different cultural backgrounds requires an adaptation process so that the measurement results are valid and reliable, but until now, there has been no research on the adaptation of subjective career success measurement tools in Indonesia. The purpose of this study is to obtain a standardized subjective career success measurement tool. The adaptation process was carried out using the International Test Commission reference in2016. Based on the results of the CFA analysis of the LISREL 8.8 program, it can be concluded that according to theory, subjective career success models have a good fit model. This means that the zero hypotheses that state the subjective career success model of the goodness of fit are acceptable. This explains that the resulting model can describe actual conditions and can be used to measure subjective career success.